Association of pre- and early post-transplant serum amino acids and metabolites of amino acids and liver transplant outcome. - Oweira, Hani; Lahdou, Imad; Opelz, Gerhard; Daniel, Volker; Terness, Peter; Schmidt, Jan; Mehrabi, Arianeb; Zidan, Ahmed; Sadeghi, Mahmoud (Transplant immunology, 2017)
Abstract: The aim of the present study was to investigate association of serum amino (AA) acids and metabolites of AAs with post-transplant outcome in...